2021
DOI: 10.3390/ijerph182413383
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Soil Solution Properties and Cu2+ Co-Existence on the Adsorption of Sulfadiazine onto Paddy Soil

Abstract: Paddy soils are globally distributed and saturated with water long term, which is different from most terrestrial ecosystems. To better understand the environmental risks of antibiotics in paddy soils, this study chose sulfadiazine (SDZ) as a typical antibiotic. We investigated its adsorption behavior and the influence of soil solution properties, such as pH conditions, dissolved organic carbon (DOC), ionic concentrations (IC), and the co-existence of Cu2+. The results indicated that (1) changes in soil soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The co-existence of antibiotics with heavy metals in the soil environment is attracting increasing attention. Xu et al [ 6 ] investigated the adsorption behavior of sulfadiazine (SDZ) in paddy soils, and found that the changes in soil pH and ion concentration decreased the adsorption of SDZ on soil components, while dissolved organic carbon (DOC) facilitated the adsorption of SDZ in paddy soils, but the effect of co-existent Cu 2+ was greatly dependent on the type of soil components. Their results confirmed that complexation may not be the only form of Cu 2+ and SDZ co-adsorption in paddy soils.…”
mentioning
confidence: 99%
“…The co-existence of antibiotics with heavy metals in the soil environment is attracting increasing attention. Xu et al [ 6 ] investigated the adsorption behavior of sulfadiazine (SDZ) in paddy soils, and found that the changes in soil pH and ion concentration decreased the adsorption of SDZ on soil components, while dissolved organic carbon (DOC) facilitated the adsorption of SDZ in paddy soils, but the effect of co-existent Cu 2+ was greatly dependent on the type of soil components. Their results confirmed that complexation may not be the only form of Cu 2+ and SDZ co-adsorption in paddy soils.…”
mentioning
confidence: 99%
“…The following supporting information can be downloaded at: , Figure S1: Absolute errors (AE) distributions of K f and K d estimation across different OC and pH ranges in sub-datasets “a” and “b” using the pedotransfer equations given in Table 4 ; Table S1: Statistical characteristics of basic properties of the soils used for individual target antibiotics; Table S2: SCP sorption parameters and associated soil properties; Table S3: SMT sorption parameters and associated soil properties; Table S4: SDZ sorption parameters and associated soil properties; Table S5: SMX sorption parameters and associated soil properties; Table S6: OTC sorption parameters and associated soil properties; Table S7: TC sorption parameters and associated soil properties; Table S8: CTC sorption parameters and associated soil properties; Table S9: pH distribution of the soils in sub-datasets “A” (for K f ) and “B” (for K d ) and main antibiotic species in soil water; Table S10: SDM sorption parameters, associated soil properties, and the performance of the model established for SMT in this study. References [ 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 ...…”
mentioning
confidence: 99%